2008
DOI: 10.1007/s00266-008-9191-1
|View full text |Cite
|
Sign up to set email alerts
|

3D Stereophotogrammetry Quantitative Lip Analysis

Abstract: We present a novel technique for aesthetic assessment of the lips that is objective and achieves consistency with the lips in the closed position. Males have greater lip dimensions compared with females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
3
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 22 publications
3
67
3
8
Order By: Relevance
“…Studies on the analysis of the face morphology of Asian populations showed mouth width values and upper lip vermillion height greater than those found by this present study [10,13,18], while the studies on Black and White Americans observed mouth width values more similar to those of the Brazilians and Peruvians [11,17]. The vestibular shift of maxillary incisors and canines can affect the upper and lower vermilion areas of the lips [20], therefore the assessment of the upper anterior teeth shapes is important to the study of lips stereophotogrammetry, especially when comparing different ethnicities, which may present different trends of dental positioning [21].…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Studies on the analysis of the face morphology of Asian populations showed mouth width values and upper lip vermillion height greater than those found by this present study [10,13,18], while the studies on Black and White Americans observed mouth width values more similar to those of the Brazilians and Peruvians [11,17]. The vestibular shift of maxillary incisors and canines can affect the upper and lower vermilion areas of the lips [20], therefore the assessment of the upper anterior teeth shapes is important to the study of lips stereophotogrammetry, especially when comparing different ethnicities, which may present different trends of dental positioning [21].…”
Section: Discussioncontrasting
confidence: 81%
“…The 3D stereophotogrammetry is the technique most used in current studies because it enables measuring variables with image depth, e.g. : volume, and linear/angular measurements [6,9,12,[17][18][19]. Table 2 displays the studies used in this discussion and the measurements found by the authors and the comparison with those of this present study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, the mandible breadth of Chakma females was almost similar to Santhal 12 , Manchu 13 , Evenks 14 , Mongol 15 , Korean 16 females. Three-dimensional data collected by digital indirect anthropometry were reported by Sawyer et al 17 for adult Caucasian and by Sforza et al 18 for white Italians. In comparison some values were larger some were smaller than the current ones.…”
Section: Procedures Of Measuring the Variables Studiedmentioning
confidence: 99%
“…Such difference may be due to difference in technique. The present study use photographic indirect anthropometry while Sawyer et al 17 used stereophotogrammetry and Sforza et al 18 used computerized electromagnetic digitizer. Besides these, ethnicity of the sample was also different.…”
Section: Procedures Of Measuring the Variables Studiedmentioning
confidence: 99%